Experiences of newly qualified midwives working in clinical practice during their transition period. (2nd September 2021) - Watson, Heather; Brown, Donna
Abstract : Background: With greater numbers of midwives being trained to counteract the predicted shortages, it seems that it is now more vital than ever to explore how newly qualified midwives (NQMs) describe their experiences in the clinical environment, the support they have received, and identify barriers to their development during the transition period. Aim: The aim of this study was to explore NQMs experiences of working clinically during the transition from student to qualified midwife. Method: Using a qualitative approach, eight NQMs participated in semi-structured interviews. Findings: The findings revealed four key themes that sum up the NQMs experiences: expectations and realities of the role; creating conditions for professional growth; the impact of the care environment; and limitations to creating a healthful culture. Conclusions: The clearly articulated journey that has been described by the NQMs demonstrated that there is both a need and desire to change, improve and develop the transition period for all new midwives working in clinical practice. Consideration needs to be given to more robust guidance, with some ideas for development, such as support forums for NQMs to meet up on a regular basis; advanced planned rotation with flexibility; a named preceptor/'buddy' in each clinical area; and a shared online forum to allow the NQMs to discuss and share experiences, and to signpost to any useful information or learning opportunities available.